Assessing the Impact of Quality and Marketing on Men's Apparel Purchase Choices for Product Brand Image at a National Fashion Retail Firm in Bandung - Riksa Ardiansyah; Ujang Wawan Sam Adinata Adinata; Dhea Perdana Coenraad; Lungguh Jatmika (P3M, STIE Pasundan, Bandung, Indonesia., 2025)
In today’s globalized world, fashion stands as an appealing and profitable business option. As the economy evolves, the fashion industry grows more expansive, complex, and diverse, supported by various models offered by producers. Fashion represents the daily clothing styles individuals adopt, whether for everyday life or special occasions, with the intent of enhancing personal appearance. This research investigates factors influencing consumer purchasing decisions in the fashion sector, particularly regarding Brand Image in the National Fashion Retail Company in Bandung. The study employs a quantitative approach, utilizing surveys to collect data from consumers. A diverse sample of respondents provides insights into their decision-making processes when selecting clothing. Findings reveal key factors that significantly influence consumer choices, including perceived product quality and emotional connections to brands. This research adds to existing knowledge by identifying specific elements that shape consumer behavior in fashion. Results indicate that a deeper understanding of consumer behavior can assist companies in maintaining competitive advantages in a crowded market. Moreover, the study offers recommendations for brands to tailor marketing strategies based on consumer insights, underscoring the importance of aligning product offerings with consumer needs and preferences.